The Hatcher The Use of Styrofoam Based Incubator on the Hatching Results of Nativ Chicken Eggs: Styrofoam Based Incubator on the Hatching - Andika Fitroh, Bagus; Haryono Awalokta, Andri; Awaliya Dughita, Putri; Hakim, Abdul; Mudi Widodo, Agung (Bulletin of Applied Animal Research, 2023)
The incubator is one of the tools used in the field of poultry farming. This incubator is used to increase the quantity of the number of eggs that are hatched. There are various types of incubator, namely manual, semi-automatic or automatic and each has advantages in its use depending on the handling during the hatching process. Other components from various existing used materials can also be used as incubator such as cardboard and Styrofoam, so as to reduce production costs in the hatchery business. Styrofoam is a packaging material made of polytrene which is generally white and rigid which is often used as food packaging boxes. The method were data collection was carried out by means of practice and direct measurement of hatching using media components from Styrofoam. The variables studied were fertility, hatchability, and hatching weight. The design model used was an evaluation design which included an assessment of the hatching eggs that were treated, namely T0: Eggs without treatment, T1: Eggs with washing treatment with water, T2: Eggs with washing using 90% alcohol, and T3: Eggs with shell rubbing treatment. with sandpaper. Each treatment consisted of 10 free-range chicken eggs with an average weight of 37 g/eggs. The best were shown at T0, T1, and T2, while T3 showed poor results on fertility, hatchability, and hatching weight in hatchery trials using Styrofoam as a incubator. Keywords: Incubator, hatchery, hatching eggs, Styrofoam.